Figure 12 from: Wallin H, Kvamme T, Bergsten J (2017) To be or not to be a subspecies: description of Saperda populnea lapponica ssp. n. (Coleoptera, Cerambycidae) developing in downy willow (Salix lapponum L.). ZooKeys 691: 103-148. https://doi.org/10.3897/zookeys.691.12880 - Wallin, Henrik; Kvamme, Torstein; Bergsten, Johannes (Zenodo, 2017)
Figure 12 - Host tree attacks. a extensive attacks of Saperda populnea lapponica ssp. n., on the entire stem and branches of Salix lapponum L. from Trysil: Ljørdalen, Norway b three adjacent attacks, including an exit hole, of Saperda populnea lapponica ssp. n., on a stem of Salix lapponum L. from Gällivare (Lappland), Sweden c single attacks, including exit holes, of Saperda populnea populnea (Linnaeus, 1758), on a stems of Populus tremula L. (beetles emerged at top: male, bottom: female), from Knivsta (Uppland), Sweden.